Progression of hepatocellular carcinoma after radiofrequency ablation: Current status of research - Wu, Shilun; Li, Zhuxin; Yao, Changyu; Dong, Shuying; Gao, Jun; Ke, Shan; Zhu, Ruhang; Huang, Sen; Wang, Shaohong; Xu, Li; Ye, Chen; Kong, Jian; et al. (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) remains an important disease for health care systems in view of its high morbidity, mortality, and increasing incidence worldwide. Radiofrequency ablation (RFA) is preferred to surgery as a local treatment for HCC because it is safer, less traumatic, less painful, better tolerated, causes fewer adverse reactions, and allows more rapid postoperative recovery. The biggest shortcoming of RFA when used to treat HCC is the high incidence of residual tumor, which is often attributed to the vascular thermal deposition effect, the wide infiltration zone of peripheral venules, and the distance between satellite foci and the main focus of the cancer. Recurrence and progression of the residual tumor is the most important determinant of the prognosis. Therefore, it is important to be aware of the risk of recurrence and to improve the efficacy of RFA. This review summarizes the relevant literature and the possible mechanisms involved in progression of HCC after RFA. Current studies have demonstrated that multimodal treatments which RFA combined with other anti-cancer approaches can prevent progression of HCC after RFA.